Relay of retrograde synaptogenic signals through axonal transport of BMP receptors. - Smith, R.B.; Machamer, J.B.; Kim, N.C.; Hays, T.S.; Marqués, G. (Journal of Cell Science, 2012)
Neuronal function depends on the retrograde relay of growth and survival signals from the synaptic terminal, where the neuron interacts with its targets, to the nucleus, where gene transcription is regulated. Activation of the Bone Morphogenetic Protein (BMP) pathway at the Drosophila larval neuromuscular junction results in nuclear accumulation of the phosphorylated form of the transcription factor Mad in the motoneuron nucleus. This in turn regulates transcription of genes that control synaptic growth. How BMP signaling at the synaptic terminal is relayed to the cell body and nucleus of the motoneuron to regulate transcription is unknown. We show that the BMP receptors are endocytosed at the synaptic terminal and transported retrogradely along the axon. Furthermore, this transport is dependent on BMP pathway activity, as it decreases in the absence of ligand or receptors. We further demonstrate that receptor traffic is severely impaired when Dynein motors are inhibited, a condition that has previously been shown to block BMP pathway activation. In contrast to these results, we find no evidence for transport of phosphorylated Mad along the axons, and axonal traffic of Mad is not affected in mutants defective in BMP signaling or retrograde transport. These data support a model in which complexes of activated BMP receptors are actively transported along the axon towards the cell body to relay the synaptogenic signal, and that phosphorylated Mad at the synaptic terminal and cell body represent two distinct molecular populations.